Unlocking mRNA Vaccine Potential in Liver Cancer Treatment via Synergistic Bile Acid Modulation - Yuqian Wang; Rui Han; Changquan Ling (Vaccines)
This Letter to the Editor explores synergistic mechanisms enhancing mRNA cancer vaccine efficacy through bile acid metabolism modulation in liver cancer treatment. The latest evidence indicates that bile acids significantly impair T cell function within the liver cancer microenvironment, creating an immunosuppressive milieu that hampers anti-tumor responses. Modulating bile acid composition, particularly increasing ursodeoxycholic acid (UDCA), could reshape the tumor microenvironment (TME) to favor mRNA vaccine-induced T cell activity—a promising strategy to overcome current immunotherapy limitations in liver cancer.